Respostas
respondido por:
0
Resposta:
Queeeeeeeeeeeeeeeee?????
respondido por:
2
Resposta:
x = 5
Explicação passo-a-passo:
2(x - 4) = (x + 3) - 2√[(x + 3)(x - 3)] + (x - 3)
2x - 8 = 2x - 2√(x² - 9)
2√(x² - 9) = 8
√(x² - 9) = 4
elevando ambos membros ao quadrado
x² - 9 = 16
x² = 25
x = ±5
substituindo "x" por "5" ou "-5" somente "5" verifica a equação pois
2(5 - 4) = (√8 - √2)²
2(1) = 8 -2√16 + 2
2 = 10 - 2(4)
2 = 10 - 8
2 = 2
Perguntas similares
5 anos atrás
5 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás